Core Interpersonal Patterns in Complex Trauma and the Process of Change in Psychodynamic Therapy: A Case Comparison Study - Van Nieuwenhove, Kimberly; Meganck, Reitske (Frontiers in Psychology, 2020)
We performed a case comparison study to investigate the nature of interpersonal patterns in childhood trauma and the process of change therein. We analysed three matching cases of childhood traumatic that followed a psychodynamic treatment via a mixed-methods design. We found that a) the core tendency to avoid negative reactions from others through passive behaviours emerged in all three cases, both in childhood and adulthood, b) core interpersonal patterns transpired in the interaction between patient and therapist and thereby affected the therapeutic relationship, and c) change ensued when a repetition of core interpersonal patterns was avoided and a new relational experience occurred. The accumulated findings across cases further resulted in several clinical implications and recommendations, such as the importance of the assessment of patients’ (covert) condition, responsiveness, supervision and facilitating patients’ agency, and provided several avenues for further research.